2017
DOI: 10.21577/1984-6835.20170142
|View full text |Cite
|
Sign up to set email alerts
|

Study of Anaerobic Co-digestion of Crude Glycerol and Swine Manure for the Production of Biogas

Abstract: Resumo:Glicerol bruto e dejetos suínos são efluentes produzidos em larga escala pela indústria do biodiesel e pela suinocultura, respectivamente. O aproveitamento de tais efluentes para a produção de biogás contribuiria para o aumento da oferta de combustíveis renováveis e para a mitigação das emissões de gases de efeito estufa. Diante de tal perspectiva, o presente estudo avaliou a produção de biogás a partir da codigestão anaeróbia do glicerol bruto com o dejeto de suínos através do uso de metodologia de sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Crude glycerol is difficult to treat biologically, due to its low nitrogen content and extreme pH; however, due to its high carbon content and anaerobic biodegradability, it can be used as a co-substrate in the anaerobic digestion of low-strength wastes/wastewater, such as sewage sludge. The high alkalinity level of crude glycerol with a pH of 10.3 [37], can also act as a buffer for acidic waste. Table 3 shows the studies using crude glycerol as the co-substrate in anaerobic co-digestion of wastewater sludge.…”
Section: Crude Glycerolmentioning
confidence: 99%
“…Crude glycerol is difficult to treat biologically, due to its low nitrogen content and extreme pH; however, due to its high carbon content and anaerobic biodegradability, it can be used as a co-substrate in the anaerobic digestion of low-strength wastes/wastewater, such as sewage sludge. The high alkalinity level of crude glycerol with a pH of 10.3 [37], can also act as a buffer for acidic waste. Table 3 shows the studies using crude glycerol as the co-substrate in anaerobic co-digestion of wastewater sludge.…”
Section: Crude Glycerolmentioning
confidence: 99%
“…Preliminary batch studies of the co-digestion of glycerol and a second substrate were performed by Aguilar et al, [22], using swine waste, with the results showing that biogas production and COD removal were favored by co-digestion.…”
Section: Anaerobic Co-digestionmentioning
confidence: 99%
“…So, potato peel wastes are produced from potato processing in large quantities, whereas about 8% of potato weight is produced as waste material. It was reported that about 370 million tons of potato peel wastes are generated worldwide Catalysts 2023, 13, 913 2 of 20 annually [3] and the growing increase in these wastes from potato industries poses serious environmental and disposal problems. So, the abatement of potato wastes and converting them into green sustainable product including bio-oils and methane (CH 4 ) is becoming a major issue, whereas the major constituents of potato peels are starch, non-starch polysaccharide, protein, ash, and lipids [4].…”
Section: Introductionmentioning
confidence: 99%